The attitudes of parents towards children with cerebral palsy - Zych, Beata Ewa; Cepuch, Grażyna (Nursing in the 21st Century, 2015)
THE ATTITUDES OF PARENTS TOWARDS CHILDREN WITH CEREBRAL PALSYIntroduction. Cerebral palsy (CP) can be regarded as a complex group of disorders, as well as a diagnostic, therapeutic and social issue which may influence the occurrence of abnormal parental attitude that deranges child development.Aim. Obtaining the knowledge about parents’ attitudes toward children with cerebral palsy and the factors which may be related to their development.Material and methods. 71 parents of children with CP . The authors used two questionnaires assessing the parents’ attitudes – one questionnaire prepared by M. Ziemska and the other prepared by the authors . The statistical analysis was performed using Chi-squared test, Student’s t-test and Wilcoxon signed-rank test.Results. The majority of parents have abnormal parental attitude towards their children. In the helplessness scale, irrespective of age of the child, parents scored moderate rating – for children 4-6y.o. 6.08 ± 2.47; 7-12 y.o. 5.56 ± 2.92; >12y.o. 6.00 ±1.00 – all with p